Imaging Study of Pseudo-CT Synthesized From Cone-Beam CT Based on 3D CycleGAN in Radiotherapy - Sun, Hongfei; Fan, Rongbo; Li, Chunying; Lu, Zhengda; Xie, Kai; Ni, Xinye; Yang, Jianhua (Frontiers in Oncology, 2021)
Purpose: To propose a synthesis method of pseudo-CT (CTCycleGAN) images based on an improved 3D cycle generative adversarial network (CycleGAN) to solve the limitations of cone-beam CT (CBCT), which cannot be directly applied to correction of radiotherapy plans. Methods: The improved U-Net with residual connection and attention gates was used as the generator, and the discriminator was a full convolutional neural network (FCN). The imaging quality of pseudo-CT images is improved by adding 3D gradient loss function. Five-fold cross validation was performed to validate our model. Each pseudo CT generated is compared against the real CT image(ground truth CT, CTgt) of the same patient based on mean absolute error (MAE) and structural similarity index (SSIM). The dice similarity coefficient(DSC) coefficient was used to evaluate the segmentation results of pseudo CT and real CT. 3D CycleGAN performance was compared to 2D CycleGAN based on normalized mutual information(NMI) and peak signal-to-noise ratio (PSNR) metrics between the pseudo CT and CTgt images. The dosimetric accuracy of pseudo-CT images was evaluated by gamma analysis. Results: The MAE metric values between the CTCycleGAN and the real CT in five-fold cross validation are 52.03±4.26HU, 50.69±5.25HU, 52.48±4.42HU, 51.27±4.56HU and 51.65±3.97HU respectively, and the SSIM values are 0.87±0.02, 0.86±0.03, 0.85±0.02, 0.85±0.03 and 0.87±0.03 respectively. The DSC values of the segmentation of bladder, cervix, rectum and bone between CTCycleGAN and real CT images are 91.58±0.45, 88.14±1.26, 87.23±2.01, 92.59±0.33 respectively. Compared with 2D CycleGAN, the 3D CycleGAN based pseudo CT image is closer to the real image, with NMI values of 0.90±0.01 and PSNR values of 30.70±0.78. The gamma pass rate of the dose distribution between CTCycleGAN and CTgt is 97.0% (2%/2 mm). Conclusion: The pseudo CT images obtained based on the improved 3D CycleGAN have more accurate electronic density and anatomical structure.